Logic and the Limits of Philosophy in Kant and Hegel - Bohnet, C. author. aut Link
VII, 270 p.
Keywords: This text examines the boundary between logic and philosophy in Kant and Hegel. Through a detailed analysis of 'quantity', it highlights the different ways Kant and Hegel handle this boundary. Kant is consistent in maintaining this boundary, but Hegel erases it and in the process transforms both logic and philosophy.